A Flexible Network of Lipid Droplet Associated Proteins Support Embryonic Integrity of C. elegans - Cao, Zhe; Fung, Chun Wing; Mak, Ho Yi (Frontiers in Cell and Developmental Biology, 2022)
In addition to coordinating the storage and mobilization of neutral fat, lipid droplets (LDs) are conserved organelles that can accommodate additional cargos in order to support animal development. However, it is unclear if each type of cargo is matched with a specific subset of LDs. Here, we report that SEIP-1/seipin defines a subset of oocyte LDs that are required for proper eggshell formation in C. elegans. Using a photoconvertible fluorescent protein-based imaging assay, we found that SEIP-1 positive LDs were selectively depleted after fertilization, coincident of the formation of a lipid-rich permeability barrier of the eggshell. Loss of SEIP-1 function caused impenetrant embryonic arrest, which could be worsened by FAT-3/fatty acyl-CoA desaturase deficiency or suppressed by PLIN-1/Perilipin deficiency. The embryonic development of seip-1; plin-1 mutant in turn depended on the recruitment of RAB-18/Rab18 to LDs, which was not observed in wild type embryos. We propose that SEIP-1 dependent and independent mechanisms act in parallel to ensure the packaging and export of lipid-rich permeability barrier constituents, which involve LDs. The identity of these LDs, as defined by their associated proteins, exhibits unexpected plasticity that ultimately ensures the survival of embryos ex utero.